Neuroacting drugs and its pharmacological response in relation to different stress status: A review - MOUSA, YJ (Journal of the Hellenic Veterinary Medical Society, 2021)
This article intended to review many methods and types of stressors in the previous works of literaturethat describe the role of these stressors to induce modifications and alterations in the pharmacological response of the drugs acting on the nervous system (neuroacting drugs) in human and animal models. The current review focus on the different methods for inducing stress status which categorized as chemical, physical and miscellaneous stressors that affect on the well-known pharmacological response of the neuroacting drugs and by which mechanism can the stressor induce a modification in the drug target response with mentioning the findings related to changes in the pharmcologiacal response of the neuroacting drugs in previous literature. In conclusion, most studies suggest an alteration of the pharmacological response of neuroacting drugs, commonly by potentiating their efficacy and subsequent toxicity, due to different stressful methods, which may be obligated to the direct and indirect receptor modification (pharmacodynamic interaction) in addition to the direct pharmacokinetic influence on the essential parameters of absorption, distribution, metabolism, and excretion of the neuroacting drugs.